Language, Mobility and Study Abroad in the Contemporary European Context - Mitchell, Rosamond; Tyne, Henry (Routledge Studies in Applied Linguistics, 2021)
"This collection explores student mobility and study abroad programmes across Europe, presenting original research on personal, linguistic, and intercultural development during study abroad experiences. The volume synthesizes work from the 2016-2020 Cost Action 15130 'Study Abroad Research in European Perspective' research network, offering a multidisciplinary account of the intersection of language learning and study abroad in Europe amidst the changing contemporary higher education landscape, as well as new directions for future research. The initial section comprises short survey chapters outlining key themes and literature, connecting traditional study abroad research with new multilingual and transnational realities. This is supported by a main section containing original empirical studies in a wide range of European contexts and a short afterword bringing together policy and pedagogical proposals. Taken together, the collection shines a light on the impact of the internationalisation of higher education on linguistic dimensions of student mobility while including a range of lesser studied settings and languages. New insights are offered on language learning, identity, interculturality, student agency and motivation, and transnational social networks in the study abroad context. This book will be of particular interest to students, researchers and institutions interested in the intersection of language learning and study abroad, including such areas as multilingualism, higher education, and applied linguistics."